IMPLEMENTASI METODE MULTI OBJECT OPTIMIZATION ON THE BASIS OF RATIO ANALYSIS (MOORA) DALAM PENERIMAAN PESERTA DIDIK BARU SMKN 2 LHOKSEUMAWE: IMPLEMENTATION OF MOORA AS A TOOL TO HELP DETERMINE THE BEST PROSPECTIVE STUDENTS - Gilang Sidiq; Nurdin; Fajriana (LPPM Universitas Abdurrab, 2025)
SMK N 2 Lhokseumawe is a public high school located on Jln. Ocean, Kampung Jawa Lama, Banda Sakti, Lhokseumawe City, Aceh. The process of admitting new students to make it more effective, the school certainly has a scoring system with predetermined criteria. SMK N 2 Lhokseumawe itself has a data system and value selection process which makes it a problem, because the data is processed only using Microsoft Excel and calculated manually. from the test results. Therefore it is necessary to change the old system with changes to the new system. By using the SPK (Decision Support System) in the MOORA (Multi Object Optimization on The Basis of Ratio Analysisis) Method in order to optimize two or more conflicting attributes simultaneously and to make it easier for SMK N 2 Lhokseumawe in determining PPDB according to the criteria set out set. This system is supported by the PHP programming language as a system development application, and the MySQL database as data storage. The results of calculations using the MOORA method show that SMK N 2 Lhokseumawe students on behalf of Afrilia Fransciska are ranked first with a percentage of 0.305 and Beriana Amelia Febrianti is ranked last with a percentage of 0.166. very useful for SMK N 2 Lhokseumawe.